OP36 A Cross-Sectional Assessment of the Effect of the Free Older Persons' Bus Pass On Active Travel and Regular Walking Among Adults ≥60 Years in England Using Data from the National Travel Survey 2005-2008. (17th September 2012) - Coronini-Cronberg, S; Millett, C; Laverty, A; Webb, E
Abstract : Background: The benefits of physical activity for all age groups is well-documented and there is increasing interest in the promotion of incidental physical activity, such as active transport, which includes walking, cycling and use of public transport. For older adults, even small increases in activity may have significant benefits: for example, the relative risk of disability is reduced by 7% for each additional hour of relatively gentle physical activity undertaken each week. Our study assessed the potential public health benefit of the National Bus Pass, introduced in 2006, which permits free local bus travel for older adults (≥60 years) in England. Methods: Data from the year prior to the pass being introduced (2005) to the most recently available (2008) were extracted from an annual cross-sectional survey, the National Transport Survey, resulting in a sample size of 15 175 older adults. Models assessed associations between possessing a bus pass and our main outcome measures: use of active transport (walking, cycling and use of public transport), use of buses and walking three or more times a week. Since participants were sampled by household, all models were adjusted for clustering at the household level, as well as a range of confounders, including: age, sex, and socio-economic status. Results: Preliminary results show that having a free pass is significantly associated with greater use of active travel among both disadvantaged and advantaged groups. It is also associated with increased use of buses and a greater likelihood of walking three or more times a week. Conclusion: Older people in England with a free bus pass are more likely to use active transport, buses and undertake regular walking than those without, regardless of their socio-economic status. This suggests public subsidies enabling free bus travel for older persons may confer significant population health benefits through increasing incidental physical activity levels.